Pendekatan Studi Islam: Perspektif Fathi Osman Dalam Metodologi Kajian Keislaman Kontemporer - Yurna Bachtiar; Nura NurAeni; Eni Nuraeni; Dwi Suryani Kurniawan; Deliyanti Dimyati; Ridwan (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2026)
Islamic studies as a scientific discipline has experienced significant methodological development in recent decades. The complexity of Islamic teachings, encompassing theological, juridical, historical, sociological, and cultural dimensions, demands comprehensive and multidisciplinary approaches. This research aims to analyze various approaches in contemporary Islamic studies and identify the strengths and limitations of each approach. The method employed is library research with a qualitative descriptive-analytical approach. Data were collected from various relevant primary and secondary literature sources, then analyzed using content analysis and comparative methods. The research findings indicate that there are five main approaches in Islamic studies: (1) theological-normative approach emphasizing the das sollen aspect based on the Qur'an and Hadith; (2) historical approach examining the development of Islam in spatial and temporal contexts; (3) sociological approach analyzing Islam as a social phenomenon; (4) anthropological approach focusing on Islamic practices in specific cultural contexts; and (5) phenomenological approach understanding Islam from the subjective experiences of its adherents. Each approach has different epistemological and methodological assumptions, resulting in diverse interpretations. This research concludes that the integration and synthesis of various approaches produce a more holistic and multidimensional understanding of Islam as a religion, civilization, and socio-cultural phenomenon